2018
DOI: 10.1027/0227-5910/a000516
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Tabloid Newspaper Use With Endorsement of Suicide Myths, Suicide-Related Knowledge, and Stigmatizing Attitudes Toward Suicidal Individuals

Abstract: The present findings confirm that readers of tabloids are an important target group for suicide education efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 38 publications
0
12
0
1
Order By: Relevance
“…Later stages of the self-stigmatizing process, namely, self-concurrence and harm-to-self, were not significantly influenced by watching short films of news at a single point in time. However, time spent reading tabloids was associated with higher endorsement of suicide myths, a lower level of suicide-related knowledge and a higher level of stigmatizing attitudes in recent studies [45]. Therefore, it can be postulated that extensive massive confrontation with SMC over a longer period of time might have a potent effect on self-stigmatization of people with mental illness.…”
Section: Discussionmentioning
confidence: 99%
“…Later stages of the self-stigmatizing process, namely, self-concurrence and harm-to-self, were not significantly influenced by watching short films of news at a single point in time. However, time spent reading tabloids was associated with higher endorsement of suicide myths, a lower level of suicide-related knowledge and a higher level of stigmatizing attitudes in recent studies [45]. Therefore, it can be postulated that extensive massive confrontation with SMC over a longer period of time might have a potent effect on self-stigmatization of people with mental illness.…”
Section: Discussionmentioning
confidence: 99%
“…While the mass media are a powerful resource for educating the public about suicide, the general public may develop misunderstandings about suicide that are caused by media misrepresentations. For example, Till et al 38 observed that the consumption of tabloid newspapers in Austria for daily information appeared to be an independent factor in the endorsement of misconceptions and myths about suicide. While we did not assess the articles for suicide myths, we did observe substantial disparities between suicide characteristics in the population and the media.…”
Section: Discussionmentioning
confidence: 99%
“…Participants with majors of medicine, psychology, or a related discipline were found to have lower public suicide stigma. High educational levels have been found to be associated with increased suicide literacy and lower suicide stigma in a few previous studies [20,29,37]. Psychoeducational programs on suicide prevention also reduced suicide stigma [12,76,77], indicating that the impact of majors on suicide stigma may be mediated by the knowledge levels of suicide, which warrants further investigation.…”
Section: Discussionmentioning
confidence: 84%
“…A study among 3432 bereaved adults in the UK showed that previous experience of suicide bereavement increased their perceived stigma of suicide, which may lead to a higher risk of suicide ideation [36]. At the same time, being continually exposed to media depictions of suicide may increase one's endorsement of suicide myths and stigmatizing attitudes specific to cultures [37]. On the other hand, lower exposure to suicide is often associated with poorer suicide literacy [38], which has been found to be associated with stigmatizing views of people who attempt or die by suicide [38].…”
Section: Factors Associated With Suicide Stigmamentioning
confidence: 99%